Correlation Between Coronavirus Disease 2019 and Olfactory Dysfunction - Mao, Yufeng; Ye, Bin; Fan, Cui; Wu, Jichang; Wang, Beilei; Shen, Yilin; Shi, Zhihong; Xiang, Mingliang (Frontiers in Public Health, 2022)
A great number of patients with coronavirus disease 2019 (COVID-19) experience olfactory dysfunction, typically of a short duration and with a high incidence rate, during the early stages of infection with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). This kind of olfactory dysfunction appears more likely in young people and women. This study presents a review of the clinical features and pathogenic mechanism of the olfactory dysfunction related to SARS-CoV-2 infection, aiming to provide a clinical reference for the diagnosis, differential diagnosis, treatment, and prevention of olfactory dysfunction in COVID-19 patients.